2005
DOI: 10.1007/s11104-004-7244-z
|View full text |Cite
|
Sign up to set email alerts
|

The effect of deficit irrigation on seasonal variations of plant water use in Olea europaea L.

Abstract: A field experiment on olive trees (Olea europaea L.) was designed with the objective to search for an optimum irrigation scheduling by analyzing the possible effects of deficit irrigation. Treatments were: a non-irrigated control (rainfed) and three treatments that received seasonal water amount equivalent to 33 and 66% of crop evapotranspiration (ET C ) in the period August-September (respectively 33II and 66II), and 66% of ET C from late May to early October (66I-II). Atmospheric evaporative demand and soil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
35
0
5

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 48 publications
4
35
0
5
Order By: Relevance
“…The capacity to withstand severe and prolonged drought periods, however, is negatively associated with olive tree growth and productivity, owing to the decrease of assimilates under water deficit conditions. Reductions in photosynthetic performance under water stress have also been observed by several authors (Inglese et al, 1999;Patumi et al, 1999;Tognetti et al, 2005;Bacelar et al, 2006;Lavee et al, 2007;Ben Ahmed et al, 2009). …”
Section: Irrigationsupporting
confidence: 60%
“…The capacity to withstand severe and prolonged drought periods, however, is negatively associated with olive tree growth and productivity, owing to the decrease of assimilates under water deficit conditions. Reductions in photosynthetic performance under water stress have also been observed by several authors (Inglese et al, 1999;Patumi et al, 1999;Tognetti et al, 2005;Bacelar et al, 2006;Lavee et al, 2007;Ben Ahmed et al, 2009). …”
Section: Irrigationsupporting
confidence: 60%
“…Our results confirm the great sensitivity of leaf photosynthesis to drought. Reductions in photosynthetic performance under water stress have also been observed by Tognetti et al (2005), Bacelar et al (2006) and Ben Ahmed et al (2009). Following the drought stress, Se-supplemented plants showed a lower reduction in these photosynthetic parameters (A and g s ) in response to drought stress when compared with water-deficit plants.…”
Section: Discussionmentioning
confidence: 74%
“…Traditional methods employ the ETo-crop coefficient approach (ETa = EToˆKc, where ETo is the reference evapotranspiration (mm day´1) and Kc is the crop coefficient) [5,6]. The accurate estimate of ETa or latent heat flux (LE) is an important factor for establishing irrigation strategies such as regulated deficit irrigation (RDI), which has been successfully applied on olive orchards to increase water productivity and olive oil quality [7][8][9][10]. In addition, Cohen et al [11] and Ortega-Farias et al [12] indicated that the site-specific irrigation management (SSIM) can be used as a technical tool to improve water productivity.…”
Section: Introductionmentioning
confidence: 99%